Hubungan kepedulian orang tua dengan prokrastinasi akademik pada siswa - Dara Rosita; Said Nurdin; Salmiati Sulaiman; Nurul Rahma (Program Studi Bimbingan dan Konseling, FKIP, Universitas Syiah Kuala, 2021)
Parents's responsibility is not only nurturing, but also guiding and educating. Besides providing all children's learning needs, process of mentoring children learning activities is part of parents' concern and responsibility as well, that aim to increase the process of children learning activities. Parents who concern toward their children will make children more enthusiasted and motivated in learning. The availability of suffice facilities and infrastructure to support the learning process is also a supporting factor for children to accomplish learning tasks. Accomplished without postpone in doing a learning task can reduce the occurrence of academic procrastination. The current study aims to determine the relationship between parents' care and academic. procrastination in students grade VIII SMP Negeri 1 in Matangkuli Aceh Utara. The research uses a quantitative approach with descriptive and correlation methods. The research population was carried out on the entire data with a total of 150 students and a sample of 108 students. The sampling method occupied Krejcie and Morgan tables with random sampling technique. Likert scale was occupied in research intrument. The hypothesis proposed in this study is there is a negative relationship between parental concern and academic procrastination in students. The results indicate that there is a significant negative relationship between parental concern and academic procrastination in students with a correlation coefficient of r = -0.405 and p 0.000. It interprete that the higher the parental concern, the lower the academic procrastination in students. Keywords: Parental concern, academic procrastination; secondary high school student ABSTRAK Tugas orang tua tidaklah sekedar mengasuh, tetapi juga membimbing dan mendidik. Kepedulian dan tanggungjawab orang tua selain menyediakan segala kebutuhan belajar anak, juga ada proses mendampingi kegiatan pendidikan anaknya, dengan tujuan agar meningkatnya proses kegiatan belajar dalam diri anak. Orang tua yang peduli akan membuat anak lebih bersemangat dan termotivasi dalam belajarnya. Tersedianya sarana dan prasarana yang memadai dalam menunjang proses belajar juga menjadi faktor pendukung bagi anak untuk menyelesaikan tugas-tugas belajar. Tuntas tanpa menunda dalam mengerjakan suatu tugas belajar juga dapat mengurangi terjadinya prokrastinasi akademik. Penelitian ini bertujuan untuk mengetahui hubungan antara kepedulian orang tua dengan prokrastinasi akademik pada siswa kelas VIII SMP Negeri 1 di Matangkuli Aceh Utara. Penelitian menggunakan pendekatan kuantitatif dengan metode deskriptif dan korelasi. Populasi penelitian dilakukan pada keseluruhan data dengan jumlah 150 siswa dan dengan sampel sebanyak 108 siswa. Metode pengambilan sampel menggunakan tabel Krejcie dan Morgan dengan teknik random sampling. Alat pengumpulan data yang digunakan dalam bentuk skala likert. Hipotesis dalam penelitian ini adalah terdapat hubungan negatif antara kepedulian orang tua dengan prokrastinasi akademik pada siswa. Hasil penelitan ini menunjukkan bahwa terdapat hubungan yang negatif signifikan antara kepedulian orang tua dengan prokrastinasi akademik pada siswa dengan koefisien korelasi r= -0,405 dan p 0,000. Dapat diartikan semakin tinggi kepedulian orang tua maka semakin rendah prokrastinasi akademik pada siswa.